Penerapan Fungsi Organisasi Siswa Intra Sekolah (OSIS) Dalam Mewujudkan Nilai Sila Ke-Empat Pancasila di SMKN1 Batanghari: fungsi, OSIS, sila ke-empat Pancasila - Kurniawan, Muhamad rizal hari; Sutja, Akmal; Usmanto, Heri (Citizenship Education, Faculty of Education, Jambi University, 2023)
This study aims to determine the application of intra-school student organization (OSIS) functions in realizing the values ​​of the fourth precept of Pancasila at SMKN 1 Batanghari. The results of the study show that the implementation of the intra-school student organization (OSIS) function in realizing the fourth precept of Pancasila at SMKN 1 Batanghari is involving students outside the OSIS management to hold deliberations in every decision-making to carry out activities, the OSIS board also provides opportunities for students to convey ideas or opinions regarding the activity plans that have been submitted by OSIS members, conduct democratic election of OSIS chairmen and members, and be open and accept all criticism submitted by SMKN 1 Batanghari students. The first obstacle faced by the OSIS SMKN 1 Batanghari in realizing the fourth precept value in Pancasila is that there are students who are less active in participating in every OSIS activity, both in deliberation activities and other activities, and students who take part in deliberation activities tend to be less active in providing criticism and opinions. The conclusion of the application of the intra-school student organization function (OSIS) in implementing the fourth precept of Pancasila at SMKN 1 Batanghari is carried out by carrying out deliberations, carrying out elections and accepting criticism. From these three aspects, the function of carrying out deliberations and carrying out elections has been carried out properly , while the function of receiving criticism has not been carried out properly.